THE PSYCHOLOGICAL CONNECTION BETWEEN SELF-AWARENESS AND PERSONAL GROWTH - Xolbutayeva Pokiza Murodulla qizi (Bright Mind Publishing, 2025)
This paper explores the deep psychological connection between self-awareness and personal growth, highlighting how the ability to reflect on one’s inner experiences contributes to emotional, cognitive, and behavioral development. Drawing on theories from emotional intelligence, humanistic psychology, cognitive-behavioral approaches, and developmental psychology, the study shows that self-awareness is foundational for identity formation, emotional regulation, mental well-being, and goal setting. It also emphasizes how practices such as mindfulness, journaling, and therapy enhance personal transformation. Ultimately, self-awareness is not only essential for understanding oneself but also for fostering a life of purpose, resilience, and continuous self-improvement.
Keywords: Self-awareness, personal growth, emotional intelligence, psychological development, identity, cognitive-behavioral therapy, mindfulness, self-reflection, emotional regulation, humanistic psychology.